Preparation of basketball players with the use of electronic aids in the conditions of a higher educational institution - I.N. Sobko; M. Krzheminskii; M. Ceslitska; R. Mushketa (H.S. Skovoroda Kharkiv National Pedagogical University, 2017)
Sobko I.N., Krzeminski M., Muszkieta R., Cieślicka M. Preparation of basketball players with the use of electronic benefits in the conditions of a higher educational institution. The application of electronic teaching aids and audiovisual teaching methods for the students of the basketball section is considered. The study involved students of the II course of the Kharkov National Economic University. S. Kuznets in the number of 120 people. In September 2015-2016 academic year, students who are engaged in the basketball section were provided with electronic manuals and video lessons on various topics of the program. At the end of the school year, students were interviewed about the effectiveness of the use of electronic educational publications. It is shown that the introduction of electronic publications in the educational process aroused great interest among students; 91.6% of students stressed that the use of electronic resources led to a better understanding of theoretical knowledge, ideas about the means and methods of teaching. High visual representation and accessibility in the use of electronic manuals increased the students' interest in classes, which stimulated the improvement of the effectiveness of the formation of practical skills. Conclusions. The use of electronic benefits in the educational process of students basketball activates the educational process, allows you to visualize the educational information, monitor the learning outcomes of the training material, which contributes to improving the effectiveness of training.